ANALISIS KEUNTUNGAN DAN TITIK IMPAS USAHA TERNAK BROILER DENGAN POLA KEMITRAAN (Studi Kasus di Desa Tetey Kecamatan Dimembe) - Hasan, Wiwit; Salendu, A H.S; Santa, N M; Oroh, F N.S (Universitas Sam Ratulangi, 2018)
ABSTRACT ANALYSIS OF PROFIT AND BREAK-EVEN ON BROILER FARM WITH BUSINESS PARTNERSHIP PATTERN (Case Study at Tetey village, Dimembe District of North Minahasa Regency). The objectives of this study were 1) to determine the pattern of partnerships business broiler farm at Tetey village with DMC company, 2) to analyze the profit of broiler farms run through a partnership pattern, 3) to analyze the breakeven point on a broiler farm run through a partnership pattern. Case study method was used on broiler chicken farm with the partnership model. The primary data obtained through observation and direct interviews with business owners of broiler chicken farms by using a questionaire. Secondary data were obtained from agencies associated with this research such as the Office of Agriculture, District Office. The results of study revealed that 1) Partnership pattern run by broiler breeders at Tetey village provided the doc, as many as 10,000 heads / period, including feed, vitamins and medicines, while farmers supplied cage and supplies, water, electricity, as well as labor and land. In addition, Broiler prices were IDR 18,000 / kg as fix price, 2) total profit of broiler farm at Tetey village through a partnership pattern were IDR 53,159,675 / period or IDR 22,149,685 / month, and 3) the number of breakeven point on broiler farm at Tetey village run with a partnership pattern were 18,691 head, or on the sale of IDR 958,644, 442.Keywords: breakeven point, partnership pattern, broiler farm.